Three Peoples, One King : Loyalists, Indians, and Slaves in the Revolutionary South, 1775-1782 - Piecuch, Jim (Book collections on Project MUSE., 2008)
"Three Peoples, One King explores the contributions and conjoined fates of Loyalists, Indians, and slaves who stood with the British Empire in the Deep South colonies during the American Revolution. Challenging the traditional view that British efforts to regain control of the southern colonies were undermined by a lack of local support, Jim Piecuch attributes the ultimate failure of the Crown's southern campaign to the ruthless program of violent suppression of Loyalist forces carried out by the revolutionaries and to Britain's inability to capitalize fully on the support available. In the process of revisiting some cherished opinions respecting the revolution, Piecuch provides a compelling alternative to long held notions of heroism and villainy in America's war for independence." "Aided by thirty-one illustrations and maps, Piecuch's pathbreaking study will appeal to scholars and students of American history as well as Revolutionary War enthusiasts open to hearing an opposing perspective."--Jacket.